Metal distribution in tissues of free‐range chickens near a lead–zinc mine in Kabwe, Zambia. (21st November 2012) - Yabe, John; Nakayama, Shouta M.M.; Ikenaka, Yoshinori; Muzandu, Kaampwe; Choongo, Kennedy; Mainda, Geoffrey; Kabeta, Matthew; Ishizuka, Mayumi; Umemura, Takashi
Abstract: Concentrations of Pb, Cd, and other metals in tissues of 17 free‐range and 32 commercial broiler chickens from the Kabwe mining town in Zambia were determined. Mean concentrations of Pb and Cd exceeded maximum levels for human consumption in some organs including muscle (Pb only) in free‐range chickens, in contrast to low levels in broiler chickens. Human consumers in Kabwe could be exposed to Pb and Cd in free‐range chickens. Environ. Toxicol. Chem. 2013;32:189–192. © 2012 SETAC